Wear-fatigue test methods and their significance - Bahdanovich, A.V.; Tyurin, S.A.; Andriyashin, V.A.; Elavyi, A.M. (Проблемы прочности, 2009)
The unified methods of wear-fatigue tests of models of active systems, which are based on a combination of the known mechanical fatigue, friction and wear test methods, are offered. A bending fatigue test method for a uniform cylindrical specimen with a test portion diameter of 10 mm is adopted as a basic one.